Analisis Perbandingan Performa Sistem Pakar Zakat menggunakan Algoritma Rule-Based dan Algoritma Rete Berbasis Web - Farisi Dharmawan; Hira Meidia (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
Web-based expert system developed in this research aims to calculate zakat based on Islam rules, and then compare two algorithms as inference machines, i.e. rule-based algorithm and rete algorithm. The advantages of this expert system are in the way of inputting data, brief explanation about end result, and javascript feature in adding the expertise of the system. In comparing two algorithms, performance parameters used are storage usage in RAM, speed in resulting conclusion, and the accuracy of conclusion, that provided by each algorithm. Pursuing a few iterations in rete algorithm has shown generally better performance compared to rule-based algorithm. This is caused by the fact that several conditions are stored in rete algorithm so that it was not needed to recalculate. Index Terms—zakat expert system, rule-based expert system, rete algorithm